ASSESSING THE IMPACT OF COVID-19 AND LOCKDOWN ON FINANCIAL WELL-BEING AND MENTAL HEALTH - Rabbani, Fazale; Mehreen, Sumaira; Azeemi, Mukhtar-ul-Haq; Shafiq, Areaba; Nazar, Zahid (Journal of Postgraduate Medical Institute, 2024)
Objective: To identify the relationship between financial well-being, demographic variables and mental health problems (depression, anxiety, and stress) and its severity level in psychiatric out and in-patients as a result of COVID-19 and lockdown. Methodology: A cross-sectional study was conducted at Department of Psychiatry, Lady Reading Hospital, Peshawar, Pakistan, from 2020 to 21 to find the association between financial well-being and mental health including (depression, anxiety, and stress) during COVID-19 ipandemic and the lockdown policies introduced in March 2020. A convenient sampling technique was used. Depression, Anxiety, and Stress Scale (DASS-21) and financial well-being scale was used for data collection. Results: A total of 261 study cases included in this study, with mean age of 27.86+8.94. Financial status of 63.6% patients were low. The prevalence of mental health issues, with 230 (88.12%) reporting depression, 225 (86.21%) anxiety, and 196 (75.10%) stress. A significant difference was found between lower financial status with depression (OR = 4.0, p < 0.001) and stress (OR = 8.0, p < 0.001), whereas there was no statistically significant association was found between anxiety and lower financial status (OR = 2.0, p = 0.068). There was a positive association observed between gender and anxiety (p = 0.028). Conclusion: Findings highlight the significant effects that COVID-19 and the ensuing lockdown measures had on people's mental and financial health. People with lower financial status had four times higher likelihood of experiencing depression, anxiety two times higher and stress eight times higher in individuals and gender differences were observed in anxiety and stress. Results underscore the interdependence of these two domains and the necessity of focused efforts to deal with the challenges the pandemic has brought forth.